Subliminal Smells Can Guide Social Preferences - Li, Wen; Moallem, Isabel; Paller, Ken A.; Gottfried, Jay A. (Psychological science, 2007)
It is widely accepted that unconscious processes can modulate judgments and behavior, but do such influences affect one's daily interactions with other people? Given that olfactory information has relatively direct access to cortical and subcortical emotional circuits, we tested whether the affective content of subliminal odors alters social preferences. Participants rated the likeability of neutral faces after smelling pleasant, neutral, or unpleasant odors delivered below detection thresholds. Odor affect significantly shifted likeability ratings only for those participants lacking conscious awareness of the smells, as verified by chance-level trial-by-trial performance on an odor-detection task. Across participants, the magnitude of this priming effect decreased as sensitivity for odor detection increased. In contrast, heart rate responses tracked odor valence independently of odor awareness. These results indicate that social preferences are subject to influences from odors that escape awareness, whereas the availability of conscious odor information may disrupt such effects.